Sustainability in agriculture management: role of social enterprises in creating a better world - Muhammad Aminuddin; Muhammad Afiq Najmi; Amirul Ashraf (Penerbit Universiti Kebangsaan Malaysia, 2024)
Social enterprises promoting sustainability in agriculture management have evolved and aligned with marginalization over decades. Due to social science criticism, the social component has been progressively incorporated into sustainability concepts and assessments However, this advancement has yet to result in a comprehensive knowledge of the social component. Thus, this paper aims to examine how social enterprises help in managing agriculture sustainably and improve the globe. A quantitative method is employed in this paper with 96 respondents as well as considering primary data in identifying key factors and practices social enterprises adopt to enhance sustainability in agricultural practices. These businesses use their strategies to address environmental, social, and economic issues. Social enterprises help the agriculture industry transform for the better by including practices such as fair salaries, environmentally friendly production, waste reduction, and community assistance. Their efforts are exemplified by organizations like Fair Trade USA, Alter Eco, and The Rainforest Foundation. The difficulties faced include needing more capital, complicated regulations, and competition from non-sustainable enterprises. Cooperative collaborations with established businesses and authorities can resolve these problems. A distinct mission, solid connections, openness, partnerships, and efficient marketing are essential success criteria. Consumers play a crucial part in assisting these businesses by purchasing sustainable goods, raising awareness, and pushing for change. The report highlights social enterprises' potential to move agriculture towards sustainability and makes suggestions for improvement. It investigates how social enterprises affect several facets of sustainable agriculture, including community empowerment, environmental preservation, and mitigating climate change. In order to reach a more sustainable future, stakeholders must continue to support social enterprises, which are critical to advancing sustainability in agriculture. Lastly, my findings on this research are social enterprises could play a significant role in promoting sustainability in agriculture management, challenges faced by social enterprises in the agriculture sector, types of collaborations by social enterprises, and factors to successful collaboration.